Shakespeare: Revising and Re-visioning - Clare, Janet (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2012)
This article engages with one of the current critical and bibliographical concerns of Shakespeare studies: the collaborative nature of Shakespeare’s work. Bibliographers have identified other hands in the fabric of Shakespeare’s plays. Here the focus is Shakespeare’s collaboration in the plays of others. Three such instances will be examined; The Book of Sir Thomas More, The Spanish Tragedy and The Chronicle History of King Lear. Substantially different as these cases may be, in all of them Shakespeare is working with the materials of others. Shakespeare’s King Lear is an adaptation of the older Leir play performed by the Queen’s Men and in that sense it is a deeply collaborative work. As this essay concludes, without a model there would be nothing to stimulate, or provoke or exceed.